2015
DOI: 10.2174/1871523014666150820100212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Screening for Analgesic and Anti-inflammatory activities of 2, 5-disubstituted 1, 3, 4-oxadiazole derivatives

Abstract: The aim of the present investigation was to synthesize, characterize and evaluate analgesic and anti- inflammatory activities of 2, 5-disubstituted 1, 3, 4-oxadiazole derivatives. The reaction of starting material 4-chloro-m-cresol with ethyl chloroacetate in dry acetone affords ethyl (4-chloro-3-methylphenoxy) acetate, which after reacting with the hydrazine hydrate in ethanol yields 2(4-chloro-3-methylphenoxy) acetohydrazide. When 2(4-chloro-3-methylphenoxy) acetohydrazide was treated with different aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In our recent study, we observed analgesic and anti‐inflammatory activities of 1,3,4‐oxadiazole derivatives . Further, we linked 1,3,4‐oxadiazole with quinazolin‐4‐one moieties and noticed significant analgesic and anti‐inflammatory activities as compared with 1,3,4‐oxadiazole derivatives .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In our recent study, we observed analgesic and anti‐inflammatory activities of 1,3,4‐oxadiazole derivatives . Further, we linked 1,3,4‐oxadiazole with quinazolin‐4‐one moieties and noticed significant analgesic and anti‐inflammatory activities as compared with 1,3,4‐oxadiazole derivatives .…”
Section: Resultsmentioning
confidence: 79%
“…Therefore, we have attempted to develop the derivatives of oxadiazole nucleus at 2‐position and 5‐postion with a view to evaluate further the potency of the molecules. In our previous study , we have synthesized 1,3,4‐oxadiazole derivatives. These agents produced up to 47% inhibition of acetic acid‐induced writhing reflex and up to 41% inhibition of carrageenan‐induced paw edema.…”
Section: Resultsmentioning
confidence: 99%
“…The analgesic activity was performed according to the protocol given by Dewangan et al . Animals were randomly divided into three groups: (A) Control [acetic acid treated ( n = 6)], (B) 1,2,4‐triazole derivatives + acetic acid treated ( n = 6) and (C) Acetyl salicylic acid + acetic acid treated ( n = 6).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Synthesis of 1,3,4-oxadiazole containing compounds and investigation of their chemical and biological properties has accelerated in recent years. 1,3,4-Oxadiazole represents an important class of biologically active species which exhibits antibacterial [1], antibiotic [2], antiviral [3], anti inflammatory [4], pesticidal [5], antiallergic [6], analgesic [7,8], ocular hypotensive [9], antimalarial [10], anticancer [11,12], anticonvulsant [13,14], antitumor [15][16][17], herbicidal [18], angiogenesis inhibitor [19], antiedema [20], anti obesity [21], antioxidant [22], anti-infective [23], anti HIV [24], antiparasitic [25], antihyperglycemic [26], anxiolytic [27],antidepressant [28], antiproliferative [29], antiplatelet [30] and gastric antisecretory activities [31]. Most of the drugs which are available in the market contains 1,3,4-oxadiazole unit.…”
Section: Introductionmentioning
confidence: 99%